The Elderly’s Anxiety Levels during the Pandemic - Fitri Suciana; Supardi Supardi; Nur Choiriyah (UNUSA Press, 2022)
The covid-19 pandemic occurred in early 2020 in Indonesia. In 2021, the number of confirmed covid-19 patients has increased. The pandemic had an impact on various sectors, such as the economy, education, society and psychology. The impact of covid19 has caused social and psychological problems for everyone, including the elderly. One of the impacts on the elderly is anxiety that affect the body’s immunity and becomes comorbid. This study used a descriptive quantitative research design. Total sampling was 46 respondents with criteria aged over 60 years. The instrument used the HRSA instruments to measure anxiety. The results showed that the average age of the respondents was 70 years, with the most gender being female (56.3%), the last education was elementary school (73.9%), most of the respondents were not working (54.3%) and anxiety levels was low anxiety (34.9%). Anxiety in the elderly was caused by excessive worrying because of a situation, and this excessive worry can decrease the body’s immunity resulting in the body being susceptible to infection with viruses or bacteria. It can cause the elderly to become comorbid infected with covid-19 viruses.